Tolerance and Adaptability of Tomato Genotypes to Saline Irrigation - Da Silva Oliveira, Carlos Eduardo [UNESP]; Zoz, Tiago; Jalal, Arshad [UNESP]; Vendruscolo, Eduardo Pradi; Nogueira, Thiago Assis Rodrigues [UNESP]; Jani, Arun Dilipkumar; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2022)
High salt concentration in irrigation water is often a limiting factor to tomato production in Brazil. However, there is limited information available regarding the tolerance of tomato genotypes to saline irrigation. An experiment was conducted in a protected environment using a randomized block design with four replications. Treatments consisted of 12 tomato genotypes cultivated in an environment with varying levels of salt stress. Moderate and severe salt stress affected plant height, transversal and longitudinal diameter of fruit, fresh mass, yield, and number of tomato fruit per plant. Cluster analysis, stability, and adaptability provided the best estimates to identify the most adaptable genotype to saline stress, with the genotypes Maestrina, Onix, Pizzadoro, and Shanty being the best adapted to moderate and severe saline stress conditions. The genotypes Maestrina, Onix, Pizzadoro, and Shanty were identified as most adaptable to and stable under salt stress. Sodium absorption increased as irrigation salinity increased. In addition, P, K, and Ca concentration decreased under salt stress, which caused damage to all yield components and plant nutrition. The genotype Onix was more tolerant to the effects of moderate saline irrigation, while the genotypes Sheena, Sperare, Santa Clara, IPA 6, and Dominador had lower losses under severe salt stress conditions.
Keywords: genotypic tolerance; N, Ca and K concentration; Na+ toxicity; stability index